Who influences government spending in agriculture? The roles of public actors in subnational funding allocation in Nigeria - Olofinbiyi, Tolulope; Mogues, Tewodaj (International Food Policy Research Institute, 2016)
This study contributes to filling the knowledge gap on the determinants of public spending. It draws on the frame-work of actor-centered institutionalism to empirically examine how the characteristics, incentives, and exchanges of different actors affect the prioritization of public investments. The study also provides insights into how the characteristics of public investments interface with actors’ incentives to influence expenditure choices.